2006
DOI: 10.1086/502972
|View full text |Cite
|
Sign up to set email alerts
|

Both CD4+and CD8+T Cells Can Mediate Vaccine‐Induced Protection againstCoccidioides immitisInfection in Mice

Abstract: To determine which lymphocytes are required for vaccine-induced immunity to coccidioidomycosis, we used a temperature-sensitive mutant of Coccidioides immitis to immunize mice lacking subsets of lymphocytes or specific cytokines and infected the mice 4 weeks later with virulent C. immitis. After 2 weeks, we determined the number of fungi in their lungs and spleens. Vaccine-induced immunity required alpha beta T lymphocytes. beta -2 microglobulin knockout (KO) mice were protected by immunization, and we transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 49 publications
5
47
0
Order By: Relevance
“…Several thorough reviews on progress toward a candidate vaccine have been published previously (4,5,208). Since then, additional studies, particularly in mice vaccinated with a variety of recombinant antigens and administered a Th1-biased adjuvant, have resulted in various degrees of protection and an increasing understanding of how protection is induced (14,120,132,136,(209)(210)(211)(212)(213)(214)(215)(216)(217)(218). This work continues to support the possibility that a vaccine candidate could be identified as suitable for clinical trials.…”
Section: Current Status Of Clinical Vaccines To Prevent Coccidioidomymentioning
confidence: 88%
“…Several thorough reviews on progress toward a candidate vaccine have been published previously (4,5,208). Since then, additional studies, particularly in mice vaccinated with a variety of recombinant antigens and administered a Th1-biased adjuvant, have resulted in various degrees of protection and an increasing understanding of how protection is induced (14,120,132,136,(209)(210)(211)(212)(213)(214)(215)(216)(217)(218). This work continues to support the possibility that a vaccine candidate could be identified as suitable for clinical trials.…”
Section: Current Status Of Clinical Vaccines To Prevent Coccidioidomymentioning
confidence: 88%
“…Murine studies have shown that both CD8 + and CD4 + T cells mediate memory responses to fungi via the production of effector cytokines, such as IFN-γ, and, in the case of CD8 + T cells, through cytotoxic activity against fungus-laden cells (7)(8)(9)(10)(11). The requirement for IFN-γ in vaccine-mediated resistance was confirmed by vaccination of Ifng -/-or Il17ra -/-mice with Aspergillus conidia or Pep1p.…”
Section: Cd8 + T Cell Vaccination Against a Fumigatus Is Defective Imentioning
confidence: 95%
“…Left lungs in these studies were used for histopathology. Though D2 mice appeared to be the most resistant of inbred strains previously tested using intraperitoneal infection (15), with an intranasal challenge of 50 spores they showed weight loss (average, 3.6 g; range, 2.0 to 5.0 g) and disease scores (average, 2.25; range, 2 to 3) similar to those of B6 mice (average weight loss, 3.4 g; range, 0.05 to 5.5 g; average disease score, 3.0; range, 2 to 4). Also, assessment at necropsy indicated extensive pulmonary involvement of D2 mice, similar to results for B6 mice, in spite of significantly lower numbers of CFU (P Ͻ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the PV/PB lymphocytic cuffs appear to be associated with the successful immune response to coccidioidal infection in SW mice and vaccinated B6 mice, while the disappearance of T cells in unvaccinated B6 mice seems to be associated with failure. In research by others, T cells are highly associated with a successful response to coccidioidal infection and adoptive immunity can be transferred by immune splenic T cells but not by B cells or immune serum (4,5,7,15). As disease progressed rapidly toward death in the B6 mice, intralesional T-cell populations virtually disappeared, B cells decreased moderately, and the PV/PB cuffing diminished to relatively thin layers of lymphocytes that consisted mostly of B cells.…”
Section: Discussionmentioning
confidence: 99%